Skeletal stability of inter-molar mandibular distraction osteogenesis in growing patients - Matthew Lewis; Peter Lewis; Tung Nguyen; Alethea Rea; Mithran S. Goonewardene (SpringerOpen, 2024)
Abstract Introduction The aim of this retrospective study was to firstly assess the stability of surgical advancement using inter-molar mandibular distraction osteogenesis (IMDO) and secondly to assess the impact of the surgical intervention on subsequent mandibular growth in patients with residual growth. Methods The sample consisted of 17 (13F and 4M) consecutively treated patients who underwent IMDO and orthodontic treatment. Cephalometric analysis was performed at three time points: T0 prior to distraction; T1 post-distraction immediately prior to surgical removal of the distractors; and T2 following completion of orthodontic treatment when the final lateral cephalogram was taken (0.86-4.37 years after T1). Statistical comparison of lower facial height, mandibular length, growth, condylar position and anterior mandibular rotation was performed. Results No association was found between changes in any of the cephalometric measurements and the length of the follow-up interval. The anterior mandibular segment underwent clockwise rotation during distraction and recovered to near its pre-distraction angulation during remodelling. An increase in the lower facial height of 1.88 ± 2.81mm also occurred during distraction (T0-T1) and was maintained during the follow-up period (T1-T2). Post-distraction (T1-T2) growth of lower facial height (p value 0.872) and mandibular length (p value 0.251) showed no association when compared to an untreated control group and an overall reduction in growth was reported. Conclusions IMDO was highly stable within a follow-up period of 2.3 ± 0.9 years; however, growth appears to have been inhibited.